THE INFLUENCE OF PRICE PERCEPTION AND ELECTRONIC WORD OF MOUTH ON CONSUMER PURCHASE DECISION THROUGH E-COMMERCE IN MALANG CITY (STUDY AT SHOPEEFOOD SERVICES IN SHOPEE E-COMMERCE) - Cholista Ferry Irawan; Rachman Hartono; Silvana Maulidah; Riyanti Isaskar (Agricultural Socio-Economics Journal, 2023)
Technological developments in the era of globalization have provided changes for society both in social, economic, and cultural aspects. This massive technological development has created unprecedented new job and business opportunities. One of the business potentials created by the massive development of information technology is the emergence of a business opportunity through e-commerce. This study focuses on the Shopeefood service. This study's objective was to investigate the influence of price perception "and electronic word of mouthâ€ on consumer purchase decisions. This study employs a quantitative methodology and data collection strategies using online surveys through questionnaires. The data in this study were analyzed using SEM-PLS. This research was conducted in Malang City from April to May 2022. This study used three variables, namely price perception (X1) and Electronic Word of Mouth (X2) as exogenous variables and purchase decision (Y1) as endogenous variables. This research proves that/price perception and e-WOM/have a significant effect on purchase decisions. With a "path coefficientâ€ value of 53% and a P-Value of 0.01, the price perception variable strongly significantly influences the decision to buy. With a path/coefficient value of 17% and a P-Value of 0.03, the e-WOM variable significantly affects consumer decision-making.